Lifetime risk, sex and age differences in annual incidence of ocular motor cranial nerve palsy in Japan for 2019 - Manabu Miyata; Ai Kido; Masahiro Miyake; Hiroshi Tamura; Takuro Kamei; Saori Wada; Hiroaki Ueshima; Shinya Nakao; Akinari Yamamoto; Kenji Suda; Eri Nakano; Miho Tagawa; et al. (Communications Medicine)
Abstract Background We aimed to demonstrate the incidence and subtype proportions of ocular motor cranial nerve palsy (OMCNP) by age group and sex, and to estimate the associated lifetime risks in the Japanese population. Methods This nationwide, population-based, cross-sectional cohort study utilized data from the National Database of Health Insurance Claims and Specific Health Checkups of Japan, provided by the Ministry of Health, Labour and Welfare, covering almost all (≥95%) claims. We identified newly diagnosed OMCNP cases (oculomotor, trochlear, or abducens palsy) between January 1 and December 31, 2019, separated by sex and age category (5-year steps). We calculated the incidence rate as the proportion relative to the Japanese population, and calculated the lifetime risk. Furthermore, we calculated the age-standardized incidence rate and lifetime risk according to the world population distribution. Results The crude incidence rate of OMCNP is 17.36 (oculomotor palsy, 6.62 [38.1%]; trochlear palsy, 2.61 [15.0%]; abducens palsy, 8.14 [46.9%]) per 100,000 person-years. The incidence rate increases with age and is higher in men than in women (19.91 vs. 14.96). The lifetime risks of oculomotor, trochlear, and abducens palsies are 0.50%, 0.19%, and 0.61%, respectively. The age-standardized incidence rates of oculomotor, trochlear, and abducens palsies are 3.25 (lifetime risk, 0.35%), 1.28 (lifetime risk, 0.13%), and 4.60 (lifetime risk, 0.45%) per 100,000 person-years, respectively. Conclusions This nationwide study of >100 million people reveals that OMCNP incidence increases with age and is higher in men. Approximately one in 100 individuals is affected in their lifetime. Our comprehensive analysis of OMCNP demographics provides important information for addressing healthcare, particularly for older people, from social and public health perspectives.